Method and facility for recovering fiber cement waste material
Through the micronization process of vertical roller mill and heating air flow, combined with air grader and screening steps, the problem of difficult to effectively remove fibers in fiber cement waste is solved, and the production of low-fiber content cement-based powder on industrial scale is realized, which is suitable for the manufacturing of medium-density and high-density fiber cement products.
Patent Information
- Application Number
- CN202380050553.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-29
- Filing Date
- 2023-06-29
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art is difficult to effectively remove fibers from fiber cement waste on an industrial scale, resulting in high fiber content in the recovered cement-based powders and failing to meet the demand for medium-density and high-density fiber cement products.
The fibers are separated from the cement-based particles through the grinding and drying process by using a vertical roller mill combined with a heating air flow micronization process, and the fibers are further separated by an air grader and a screening step to obtain a cement-based powder with a low fiber content.
The fiber content in fiber cement waste is effectively reduced on an industrial scale, and the obtained cement-based powder is suitable for the manufacture of medium-density and high-density fiber cement products without reducing or degrading calcium silicate hydrate.
Smart Images

Figure CN119604475A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the processing of fiber cement materials, in particular the processing of fiber cement waste products for recycling purposes. Background Art
[0002] Fiber cement is an important building material. Although asbestos fibers were used in the past, these fibers have been replaced by carbon-based fibers for well-documented health reasons. Cellulose fibers are a common type of carbon-based fiber used in the manufacture of fiber cement products, such as in autoclave-cured fiber cement products. Other types of carbon-based fibers include polyvinyl alcohol (PVA) fibers and polypropylene (PP) fibers, which are commonly used in air-cured fiber cement. Polyethylene (PE) fibers may also be used in combination with any of the above. The majority of fiber cement products have a density of at least 1.2 kg / dm 3 , and has been prepared as a series of thin layers which are laminated into green sheets following a curing process. For example, such structures are obtained using the Hatschek manufacturing process. The resulting fiber cement product is characterized by high compressive strength.
[0003] Waste fiber cement materials are available in large quantities, not only from use and replacement products, but even primarily as a by-product of the production technology of new products, such as cutting of newly produced fiber cement panels.
[0004] Therefore, the recovery of such waste fiber cement materials has been studied before. For the convenience of reuse, the waste materials, which are usually in the form of plates or larger pieces, will first be crushed (crush), and then pulverized (pulverize). However, fiber cement is a composite material. In order to achieve useful recovery, it is desirable to remove at least a portion of the fibers in the fiber cement product. According to JP2002-273258A1, the material can first be subjected to volume pulverization (volume pulverization). Since organic fibers have very little pulverization effect in a volumetric pulverizer, the fiber length is relatively maintained at several hundred μm. The fibers can thereafter be removed by using a specific gravity difference, particularly in an air classifier. Therein, separation is performed between the airflow in which the fibers are dispersed and the powder with a significantly reduced fiber content.
[0005] The example given in the specification of the patent for a fiber cement product uses an air classifier, which uses an open circuit. In this open circuit, material that is too coarse compared to the separation size of the air classifier is removed from the operation as a side stream. This open circuit significantly reduces the output of the separation process. Therefore, it is not efficient. The patent specification provides another example for a calcium silicate board comprising 10% pulp, using a roller mill and an air classifier in a closed circuit. However, this calcium silicate board has a low density of less than 0.9 kg / dm3, a high porosity, and is known to be easy to cut; in fact, it is not a fiber cement product because it does not contain cement or only as an additive in small amounts, such as 5% by weight.
[0006] JP2004-217482A1 discloses a method in which the particle size (median diameter) of the obtained powder is in the range of 10-35 μm. Therein, the waste material is treated in a primary comminution step using a hammer mill, followed by a secondary crushing step using a roller mill. The material then receives air classification, and after air classification, the fiber components are removed by a sieve. No further details of the method are disclosed.
[0007] The obtained powder was used to make a low density product, with a density between 1.0 and 1.1 kg / dm3. In addition, a slurry including cement, fly ash, silica stone and a pulp of short and long fibers (i.e. cellulose) and 5% of recycled powder was prepared into sheets. The excavated sheets were press-formed at 3 MPa and then first pre-cured and then autoclaved.
[0008] However, low density products are typically used for ceilings. They do not have the required properties for exterior siding, flooring applications, and / or roofing applications, which use medium and high density boards. The reported tensile strengths are in the range of 4.5-5.3 MPa, which is well below the requirements for exterior siding, flooring, and / or roofing applications. Furthermore, it is not obvious from the data that recycled materials can be used for more demanding applications.
[0009] In fact, JP2006-23624A1 is a subsequent patent publication document of the same inventors, which includes a comment on the product quality of the regenerated powder disclosed in JP2004-217482A1. It states in paragraph
[0005] that the fiber component and the solid component are usually in a tangled state in the pulverized product, and it is difficult to separate them completely. Due to the protrusion of organic fibers, this will result in a significantly large particle size. Therefore, the particle size of the pulverized product will vary, and the desired performance is given to a new manufactured product including the same pulverized product (
[0006] ). The public solution to this product is to subject the pulverized product to a heat treatment to burn and remove the organic fibers (
[0016] ). This solution obviously has other disadvantages, including: the use of energy, the treatment of air including any removed products, and the potential change of the cement matrix due to exposure to high temperatures, preferably in the range of 450 to 500°C. It is known that hardened (air-cured) cement loses its water of hydration as the temperature increases. For example, calcium hydroxide starts to lose its water of hydration from 400°C. In addition, calcium hydroxide and calcium silicate hydrate (CSH) may degrade, resulting in a loss of strength. For air-cured fiber cement, such CSH includes 2CaO.SiO2. For autoclave-cured fiber cement, CSH includes, for example, tobermorite.
[0010] Therefore, there is a need for an improved method of recycling fiber cement waste, wherein in particular fibers can be removed from cement-based powders, and this not only in experiments but also on an industrial scale. More specifically, the cement-based powders should be reusable for medium and high density fiber cement products. Furthermore, it should be applicable to feedstocks consisting mainly of high density fiber cement materials. Summary of the invention
[0011] It is therefore a first object of the present invention to provide a method for processing fiber cement waste material into a cement-based powder with a reduced fiber content relative to the waste material, which method does not have the disadvantages of the prior art.
[0012] A second object of the present invention is to provide an apparatus for processing fiber cement waste material into cement based powder.
[0013] A further object of the invention is to provide the use of the apparatus for processing waste material.
[0014] Another object of the present invention is to provide a method for processing cement waste materials
[0015] The present technology also relates to cement-based powders with reduced fiber content and without entangled fibers without reducing or degrading the calcium silicate hydrate in the cement.
[0016] The present technology also relates to the use of the cement-based powder, for example in fiber cement products or concrete products.
[0017] According to a first aspect, the present invention relates to a method for processing fiber cement waste material into cement-based powder, in particular the cement-based powder having an organic carbon content of up to 2% by weight, the method comprising the following steps:
[0018] supplying crushed material derived from fiber cement waste material to a micronizing device comprising: a vertical roller mill in a grinding chamber; means for generating an upward heated air flow through the grinding chamber; an air classifier arranged above the vertical roller mill in the grinding chamber, and an outlet downstream of the air classifier;
[0019] grinding the crushed material in a vertical roller mill to break apart the crushed material, thereby reducing the size of at least a portion of the crushed material without correspondingly reducing the size of fibers embedded in the crushed material, thereby generating agglomerates of cement-based particulate fibers,
[0020] removing material from a vertical roller mill and drying the agglomerates with the aid of an upward heated air flow, wherein fibers are released from the cementitious particles during the upward air flow and / or any subsequent impingement within a grinding chamber;
[0021] The cement-based particles are separated into a portion of larger particles and a portion of smaller particles in an air classifier, the larger particles are re-supplied to the grinding chamber of the roller mill, while the mixture of the smaller particles and the released fibers is ejected through an outlet,
[0022] The sprayed mixture is separated by sieving through a sieve to separate the fibers from the cement-based particles, thereby obtaining the cement-based powder.
[0023] The inventors have obtained surprisingly good results for this process using a vertical roller mill in combination with a heated air flow through the grinding chamber which removes the agglomerates resulting from the grinding, as well as any separated ground particles and fibers, towards an air classifier at the top of the grinding chamber. Thereafter, the fibers can be separated from the mixture.
[0024] In the grinding step of the vertical mill, the feed is broken up as a crushed material, rather than being completely ground. The fibers are not ground or not significantly ground. This results in agglomerates of fibers and cement-based particles. In particular, a roller-based grinding process is used, and the material is therefore ground by compression forces, rather than using impact-based grinding, such as a ball mill process.
[0025] As the cement-based particles and fibers bond together, agglomerates of fibers and cement-based particles are formed. The inventors believe that this bonding is due to the interaction between the particles, fibers and any moisture within the material; in other words, adhesion between the hydrophilic fibers and the cement-based particle surfaces. The fibers in fiber cement are typically hydrophilic fibers, such as cellulose fibers and polyvinyl alcohol (PVA) fibers. When the agglomerates are dried by treatment with heated air flow, adhesion is reduced and the particles can be released from the fibers and / or vice versa. Any impact, such as impact to the chamber wall or impact during processing in an air classifier, may promote this release.
[0026] In the context of the present invention, the term "agglomerate" is understood according to its meaning in surface chemistry, wherein it is relative to aggregate. Wherein aggregate is based on the strong chemical bond between the constituent elements, and agglomerate is held together by means of weak physical interactions. The constituent elements are solidified cement-based particles and fibers here. The number of fibers per agglomerate is usually limited, such as less than 10, and even less in most of the agglomerates, such as at most 5, even at most 3 or 2. In the case of a large number of fibers, this agglomerate is usually not passed through an air classifier, but is recycled to a vertical roller mill for further grinding. It is believed that agglomerates are usually such that fibers may be partially exposed to the outside of the agglomerate. Although the grinding process is designed to generate agglomerates, it is not excluded that it will further generate separated cement-based particles and / or some released fibers, and the former is more likely than the latter.
[0027] In a subsequent process step of removing the particles by means of a heated air stream and / or impact of the flowing particles against the walls of an air classifier and / or a grinding chamber, complete release of the fibers from the cement-based particles is achieved.
[0028] The size of the cementitious material is reduced roughly from about 5-15 mm to 2-100 μm, preferably with 90 wt% in the range of 5-80 μm or even 10-60 μm. The median (d50) of the resulting cementitious powder is suitably in the range of 10-60 μm, preferably in the range of 10-50 μm, even more preferably in the range of 10-40 μm, for example 20-30 μm. The upper limit of this median is determined by the fiber concentration and the average fiber length. When the average fiber length is 500 μm, the risk of fluidity problems increases significantly. The inventors believe that the increase in fluidity problems is caused by the entanglement of individual fibers, the likelihood of which increases with increasing fiber length. If the cementitious powder does not have sufficient fluidity, there is a risk that the cementitious powder may not be properly removed from the silo in which it is filled. In addition, insufficient fluidity is believed to hinder the uniform dispersion of cementitious powder in cement compositions used to make fresh products, such as fresh fiber cement products.
[0029] The reduction in fiber length is from 0.8-2.0 mm back to 0.2-0.5 mm. It is believed that crushing equipment such as hammer mills and vertical roller mills all contribute to this size reduction. As is evident from the characterization in Example 3, the fiber length in the cement-based powder obtained from the grinding and sieving steps is surprisingly uniform (i, e has low polydispersity).
[0030] In the air classifier, the coarser particles will be excluded and fall back to the vertical grinding. The finer particles and the released fibers will pass through the air classifier. Therefore, the air classifier does not provide separation of fibers and cementitious materials, but provides separation between fine cementitious materials and coarse cementitious materials. In addition, the air classifier can help to release fibers from the ground cementitious materials. It is observed that the length of the fiber may exceed the size limit of the air classifier and can therefore be regarded as part of the coarser part. However, in view of its shape and elasticity, it is also found that relatively long fibers pass through the air classifier. In addition, it is observed that no fibers or substantially no fibers are removed from the air classifier with the air flow.
[0031] In the second separation step, the separation of the released fibers and the finer cementitious material is carried out downstream of the air classifier, which is a screening step. It is observed that in this second separation step, not all fibers are removed from the finer cementitious material. However, the removal of the fibers is sufficient to reduce the fiber content, i.e. the organic carbon content, to less than 2% by weight. The organic carbon content does not include inorganic carbon, such as carbon in the form of carbonates, especially calcium carbonate. In addition, the organic carbon content is calculated based only on carbon.
[0032] In one embodiment, the grinding chamber is heated to a temperature in the range of 70-90°C. Here, the air flow itself is brought to a higher temperature. It was found that this provides heat for sufficient drying of the agglomerates during their residence time in the grinding chamber. Obviously, if less heat is provided, there will be less drying, so that more agglomerates will remain stable and may be returned to the vertical roller mill.
[0033] In another advantageous embodiment, the vertical roller mill comprises a rotating horizontal grinding track and one or more rollers, the rollers being configured to rotate about a fixed axis of rotation so that the crushed material is ground between the grinding track and the lateral surface of the rotor. The mill may also include a rotating table portion. Preferably, the lateral surface of the roller is a conical surface. The roller is thus tapered and its axis may include an angle in the range of 0-30 degrees, for example 10-20 degrees, to the grinding track. The rollers actively rotate about their respective axes of rotation and press against the rotating table portion while the crushed material is supplied to the space between the rotor and the rotating grinding track, thereby breaking and further reducing the size of the crushed material.
[0034] In another embodiment, the air classifier is a gravity air classifier. Here, the coarser particles are conveyed by gravity through a valve at the bottom of the air classifier, and the fine material is conveyed by air to a fabric filter. The air classifier may have an inner chamber from which the coarser material is discharged into an annular gap by means of centrifugal force. This will allow a subsequent downward flow. However, under such force, more fibers may be released from the cement-based particles and will not fall back into the vertical mill and be ground. The size of the coarser material to be rejected is, for example, in the range of 100-200 μm, such as 130-170 μm, for example 125 μm or 150 μm. This size can be set by means of a classification point.
[0035] In a further advantageous embodiment of the invention, the particle size (defined by the median diameter) of the crushed material is in the range of 2 mm to 10 cm, preferably in the range of 3 mm to 5 cm, such as in the range of 5 mm to 3 cm. In this way, the particle size of the crushed material is such that the fibers are mainly retained in individual pieces of the crushed material. Thus, the crushing does not reduce the length of the fibers more than is necessary to achieve a suitable feed for the vertical roller mill.
[0036] In a preferred embodiment, the method further comprises the step of crushing the waste material into a crushed material before the connection and fiber separation. The on-site crushing of the waste material provides such a benefit that some detection steps can be carried out to remove undesirable or harmful elements. In addition, this ensures that the crushed material has the preferred size specified above. In another embodiment, the step of crushing the waste material comprises a first step of breaking the waste material into agglomerate materials and a second step of breaking the agglomerate materials into crushed materials. For example, the first step can be carried out with the aid of a pulverizer. For example, the second step can be carried out with the aid of a hammer mill, but other known grinding techniques are not excluded. As used herein, agglomerate materials are materials with macroscopic dimensions, for example, diameters in the range of 5 to 25 cm, such as 10 to 15 cm. It is understood that the exact size is not important here. However, the material should be suitable as a feed for the mill used in the second step.
[0037] In another preferred embodiment, the crushed material is subjected to a detection step to remove harmful and / or undesirable materials. Any detected harmful or undesirable materials can be removed. Known options for removal include valves and grippers.
[0038] One option is to use a magnetic detection step, which is considered suitable for the removal of metals. Another and preferred option is an optical detection step, such as with the aid of a camera to detect and subsequently identify unwanted and / or harmful materials. For example, the camera can be selected to operate using visible light (400-750nm) or near infrared (NIR, 750-2000nm). A combination of the two is also feasible. In one embodiment, the detection step and the detector are configured to detect polymer strips. Such strips are used for certain types of fiber cement, such as corrugated sheets. It is believed that detection using near infrared spectroscopy is preferred, but other options are not excluded. In another embodiment, the detection step is configured to detect asbestos materials. This can be done with the aid of near infrared spectroscopy.
[0039] Preferably, the detection and removal steps are implemented in an automatic manner, i.e. without requiring operator action. As is known in the art, this is achieved by a so-called vision step utilizing optical detection software. A light source for emitting radiation of the desired wavelength may also be required, for example by means of NIR detection.
[0040] In another preferred embodiment, the separation step of removing fibers from cement-based particles by screening is performed using a mesh in the range of 50-200 microns, preferably 70-180 μm, more preferably 90-160 μm, such as 100 μm, 125 μm or 150 μm. This mesh is the best option between the maximum yield of cement-based particles and the minimum fiber content. When a 150 μm mesh is used, the fiber content can be reduced to 2% by weight of organic carbon. When a 80-100 μm mesh is used, the fiber content can be further reduced to 1% by weight of organic carbon. The exact carbon content of the resulting cement-based particles will depend on several parameters, including the content of fibers in the waste material, the type of fibers and the size of the crushed material, and the type of screen. A variety of screen types are known in the art, including dry screens, air jet screens, and screens supported by ultrasonic vibrations. Selection is made based on the effectiveness and capacity of the separation.
[0041] In a further embodiment, the sieving step can be carried out with a plurality of sieves arranged in series, wherein the mesh of the second sieve is reduced compared to the first sieve. For example, the first sieve has a mesh of 150 μm and the second sieve has a mesh of 100 μm. However, other meshes can also be chosen and the number of sieves can be greater than two. One or more intermediate portions that passed through the first sieve but not through the last sieve can subsequently be further processed, for example by means of different separation techniques, such as a classifier. Such portions can also be fed back into the grinding chamber for re-separation.
[0042] Another advantage of the present invention is that the fibers separated in the screening step can also be reused.A useful method of reusing fibers is to add those fibers to fiber cement with a concomitant reduction in fresh fiber material in the fiber cement slurry.
[0043] Preferably, the particle size distribution of the obtained cementitious powder is such that at least 90% by weight (d90) is less than 100 μm. Furthermore, the cementitious powder advantageously has a median value (d50) in the range of 10-60 μm, preferably 10-40 μm, more preferably in the range of 15-35 μm, more preferably 20-30 μm. For the avoidance of doubt, the particle size distribution is determined using a particle size analyzer supplied by Malvern Pananalytical and known as Mastersizer TM The particle size distribution is determined by laser diffraction using a device of the 3000. The particle size distribution depends on the settings of the grinding step in the vertical roller mill. The median value in the range of 10-40 μm is particularly suitable for repeated use in cement and / or fiber cement production, since it corresponds to the median particle size of cement and quartz. Furthermore, this results in the fibers in the cement-based powder having a limited length, for example an average length of less than 500 μm, and preferably in the range of 300-450 μm, as defined by the arithmetic mean length.
[0044] It has been found that cement-based powders such as those having such a particle size distribution can be used for repeated use in fiber cement, since the particle size distribution corresponds approximately to the particle size distribution of the other components of the fiber cement product, such as cement and silica. However, the resulting cement-based powder is also advantageous for use in concrete and other building materials, as will be discussed in more detail below. One of the advantages of the cement-based powder is its flowability, due to the limited number of fibers, and in particular the absence of larger fibers, such as fibers having a length of more than 700 μm, or even more than 600 μm, or even more than 500 μm. This flowability allows the cement-based powder to be stored in a silo container, and facilitates the powder to flow out of the bottom without clogging.
[0045] In addition, for example when compared with comminution by means of a ball mill, the method of the present invention has the advantage of a short throughput time for the comminution step and fiber removal. This has the further advantage that different batches of fiber cement waste materials can be processed by the method of the present invention without significant mixing. This is an important advantage because it allows the generation of cement-based powders with limited fiber content from batches of a single source, such as specific fiber cement products, or even fiber cement products of a specific color. Therefore, when using production waste, the resulting batches of cement-based powders will have a known cement component. This batch can then be reused to produce a single product, typically a product from the same source as the waste.
[0046] Furthermore, the process of the invention can already process fiber cement waste on an industrial scale with a feed of waste material in the range of 500-2000 kg / h, preferably 1000-1800 kg / h. Higher feed rates are not excluded and can obviously be achieved by adding equipment.
[0047] According to a second aspect, the invention relates to an installation comprising: an apparatus for crushing waste fiber cement material in which fibers are embedded in a cured cement matrix into a crushed material;
[0048] - a micronization device 10, comprising (1) a vertical roller mill in a grinding chamber, the vertical roller mill being configured to use the crushed material as feed and to generate agglomerates of cement-based particles and fibers; (2) means for generating an upward heated air flow through the grinding chamber, the heated air flow being used to transport upward the agglomerates of fibers and the cement-based particles, and for drying the agglomerates; (3) an air classifier, which is arranged in the grinding chamber above the vertical roller mill, for separating the coarser fraction of the cement-based particles and returning them into the grinding chamber towards the vertical roller mill, and an outlet downstream of the air classifier through which the finer fraction of the cement-based particles and the released fibers pass;
[0049] - A screen downstream of said outlet for separating said liberated fibers from said cement-based particles.
[0050] The facility is suitable and configured to carry out the process of the invention as described above. With the aid of the following figure description, the facility is described in more detail. Any features associated with the above process or described with reference to the accompanying drawings are also considered to be designated as being combined with the facility.
[0051] According to an advantageous embodiment, a vertical roller mill comprises a rotating horizontal grinding track and one or more rollers, the rollers being configured to rotate about a fixed axis of rotation while pressing against the grinding track, so that the crushed material is ground between the grinding track and the lateral surfaces of the rollers. The mill may also comprise a rotating table portion. Preferably, the lateral surfaces of the rollers are conical surfaces. The rollers are thus tapered and their axes may comprise an angle in the range of 0-30 degrees, for example 10-20 degrees, to the grinding track. The rollers actively rotate about their respective axes of rotation and press against the rotating table portion, while the crushed material is supplied to the space between the rotor and the rotating grinding track, thereby breaking and further reducing the size of the crushed material.
[0052] In another embodiment, the air classifier is a gravity air classifier. Here, the coarser particles are conveyed by gravity through a valve at the bottom of the air classifier, and the fine material is conveyed by air to a fabric filter. The air classifier may have an inner chamber from which the coarser material is discharged into an annular gap by means of centrifugal force. This will allow a subsequent downward flow. However, under such force, more fibers may be released from the cement-based particles and not fall back down into the vertical mill and be ground. The size of the coarser material to be rejected is, for example, in the range of 100-200 μm, such as 130-170 μm, for example 150 μm.
[0053] According to another advantageous embodiment, the material is transported between specific devices in the facility by means of a conveyor belt. The outlet of the micronizing device is preferably coupled to a screen by means of a channel in which air is used as a carrier for the particles and fibers. Alternatively, a conveyor belt may be used. Although in the present application reference is made to a micronizing device, it is understood that the device actually reduces the size of the fiber cement material to a range of 1-100 microns, and the median is preferably in the range of 20-30 microns.
[0054] In another embodiment, the device for crushing waste materials comprises a first stage for breaking the waste materials into agglomerated materials and a second stage for breaking the agglomerated materials into crushed materials. The first stage is implemented as a pulverizer, for example. The second stage is implemented as a hammer mill, for example.
[0055] Preferably, the screen is selected to be an ultrasonic screen. This has been found to facilitate correct operation. More preferably, the screen may be an apparatus comprising a plurality of individual screens, wherein the screen size is subsequently reduced.
[0056] In another embodiment, the facility also includes one or more detectors for detecting hazardous and / or undesirable materials. These materials include conventional undesirable materials, such as metal and plastic parts, and asbestos, which may be present in waste materials from demolished buildings and / or renovated buildings. It is desirable to prevent the resulting cement-based powder from being contaminated by any asbestos fibers.
[0057] Metals can be detected using magnetic detectors. A preferred option for such a detector is an optical detector, such as detection with the aid of a camera, and subsequent identification of unwanted and / or harmful materials by automatic image recognition. For example, the camera can be selected to operate with visible light (400-750nm) or near infrared (NIR, 750-2000nm). A combination of the two is also feasible. In one embodiment, the detection step and the detector are configured to detect polymer strips. Such strips are used for certain types of fiber cement, such as corrugated board. It is believed that detection using near infrared spectroscopy is preferred, but other options are not excluded. In another embodiment, the detector is configured to detect asbestos materials. This can be done with the aid of near infrared spectroscopy.
[0058] Preferably, one or more detection steps are implemented in an automatic manner, i.e. without the need for operator action. As is known in the art, this is achieved by a so-called vision step using optical detection software. A light source for emitting radiation of the desired wavelength may also be required, for example by means of NIR detection.
[0059] Furthermore, preferably, there is any removal device, such as a valve or a gripper, which is driven via the output signal of the detector. In this way, harmful and / or undesirable waste will be removed in an automatic manner without the need for operator action.
[0060] In a preferred embodiment, the facility is configured to process not only fiber cement waste, but also concrete, mortar, cement, but in particular concrete. This combination is beneficial to the economic operation of the facility and is also conducive to achieving optimized output. In order to process both fiber cement waste materials and concrete, the micronization device is provided with a first output for aggregate and a second output for sand and clay and mixtures thereof. There is a shifting device, so that the ground sand and clay are shifted from the vertical roller mill toward the second output. Embodiments of the shifting device include screws, pistons, buckets. The screw is considered to be a preferred option. In a further embodiment, the screw or piston can be arranged in a tube, so as to minimize the material falling from the screw. In operation, concrete will be ground into aggregate, sand, clay and / or its mixture, and cement-based particles. Aggregate will be removed via the first output, which is preferably arranged downward from the vertical roller mill. Clay, sand and / or its mixture will be removed via the second output supported by the shifting device. Cement-based particles can be removed via an air classifier.
[0061] This embodiment of the micronizing device is considered to be technically beneficial because the pretreatment, such as the device for crushing the waste material, and any additional and optionally present detectors, can be the same for different waste sources. This keeps the complexity of the entire facility at a low level. A further benefit thereof is that the separate removal of aggregate, clay and / or sand reduces the average number of grinding cycles required to grind the concrete material into particles of any desired size. A further advantage of the facility is that, in view of the short operating time of the vertical roller mill, the different feed materials can be kept separate.
[0062] In a further embodiment of the present invention, the facility is also provided with an optical detector for automatically detecting the feeding of the micronizing device. Based on the output of this detector, the setting of the micronizing device can be switched from a first state for processing concrete to a second state for processing fiber cement waste, and / or vice versa. Obviously, the switching of the setting of this micronizing device can also be realized in other ways, such as by an operator, by a software program in which an operation plan is loaded, etc. In the first state, the shifting device will be operated. The grinding pressure will be relatively high, i.e. suitable for grinding concrete. In the second state, the shifting device can be closed, and the grinding pressure will be relatively low. Optionally, the setting of the air classifier and the flow rate of the heated air can be changed between the first state and the second state.
[0063] In yet another embodiment, the screen may be provided with a bypass. When switching from the second state to the first state, the bypass may be activated so that cement-based particles from the concrete do not pass through the screen. This is believed to be beneficial to operating efficiency, as well as reducing wear and damage to the screen.
[0064] In yet another embodiment, a screening machine device may be arranged downstream of the second output for separating sand and clay. In a further embodiment, a screening device comprising a first screen and a second screen arranged in series may be present downstream of the second output. The first screen is suitably a coarse screen, such as having a diameter in the range of 0.5 to 4 mm, for example 1 to 2.5 mm. The second screen may be a fine screen, such as having a mesh in the range of 100-300 μm. In this way, the output stream of the second output may be separated into a coarser portion to be aggregated, an intermediate portion including sand and / or clay, and a fine portion. The coarser portion may be directed to the first output or recycled into the micronization device. The fine portion may be attached to cement-based particles. The intermediate portion may be further processed to separate sand and clay, preferably using a screening device.
[0065] The facility of the preferred embodiment is versatile in that a wide variety of waste materials can be processed. Furthermore, it can be efficiently processed into a plurality of output streams, each of which may be valuable and useful in one or more production processes for cement and fiber cement manufacturing. These output streams include: a cement-based powder provided with a low amount of fibers, particularly less than 2% by weight based on the organic carbon content, wherein the fibers are relatively short; a fiber stream, which mainly comprises fibers and is retained on the screen; a sand output stream, a clay output stream, an aggregate output stream from concrete, and a separated cement-based powder. Furthermore, the different feeds can be kept separate, so that production waste from fiber cement materials of gray, black, red or white color will produce gray, black, red and white output streams, respectively. In order to reduce the organic carbon content, the cement-based powder from concrete can also be mixed with the cement-based powder from the fiber cement waste.
[0066] According to a third aspect, there is provided a use of the plant according to the invention, in particular a use of a preferred embodiment thereof, wherein a first batch and a second batch of waste material are processed one after the other, wherein the first batch is concrete waste material and the second batch is fiber cement waste material. More specifically, said use comprises the step of changing the setting of the plant from a first state to a second state between the processing of the first batch and the second batch. Any other embodiment discussed above also applies to this third aspect.
[0067] According to a fourth aspect, there is provided a method for processing waste, comprising the steps of:
[0068] Providing an apparatus according to the invention, preferably according to its preferred embodiments;
[0069] processing a first batch of waste materials at a facility, wherein the first batch is concrete material;
[0070] Thereafter, a second batch of waste material is processed in the facility, wherein the second batch is fiber cement waste material.
[0071] According to the present invention, the first batch and the second batch will produce separate output streams, which can be separately recovered and can be separately reused, as explained above. According to a preferred embodiment, the method also includes the step of changing the settings in the equipment from the first state to the second state between the processing of the first batch and the processing of the second batch. The other embodiments discussed above are also applicable to this fourth aspect of the present invention.
[0072] The cementitious powder obtained using the method of the present invention generally comprises up to 2% by weight of fibers defined by the organic carbon content, wherein the particle size distribution of the powder is such that at least 90% by weight (d90) is less than 100 μm, the median (d50) is in the range of 10-40 μm, preferably in the range of 15-35 μm, more preferably 20-30 μm, and wherein the cementitious powder is a cured powder comprising at least 5% by weight of calcium hydroxide and / or calcium silicate hydrate (CSH). Furthermore, the arithmetic mean length (L(n)) of the organic fibers is in the range of 0.25 mm to 0.50 mm, preferably in the range of 0.30 mm to 0.45 mm. The content of calcium hydroxide and calcium silicate hydrate will hereinafter be referred to as CSH content. The CSH content is more preferably at least 10% by weight, further preferably at least 15% by weight. The CSH content may even be at least 20% by weight. In fact, the CSH content is related to the CSH content in the fiber cement waste material. Due to the removal of fibers, the CSH content in cement-based powders may be even higher than that in fiber cement waste material. The CSH content can be determined with the aid of X-ray diffraction analysis (XRDA).
[0073] Generally, fiber cement is cured in two different ways, namely air curing and autoclave curing. Therefore, the CSH content is different. In cement-based powders obtained from air-cured waste materials, the CSH content is mainly in the form of calcium hydroxide and CSH gel, and the calcium hydroxide is usually crystalline. As known to those skilled in the art, CSH gel is a material comprising crystals, but it behaves as a gel. In cement-based powders obtained from autoclave-cured waste materials, the CSH content will be mainly in the form of tobermorite.
[0074] Therefore, in one embodiment of the present invention, the cement-based powder is an air-cured powder and includes calcium hydroxide and CSH gel as the main CSH. In another embodiment of the present invention, the cement-based powder is an autoclave-cured powder and includes tobermorite.
[0075] In a further embodiment of the invention, the cementitious powder comprises up to 1% by weight of fibers as defined by the organic carbon content. In another embodiment, the cementitious powder comprises 0.5 to 2% by weight, preferably 1.0 to 2.0% by weight of fibers as defined by the organic carbon content. In addition to the total content, the fiber length of the fibers is believed to be highly relevant to proper flowability.
[0076] The inventors observed during the tests leading to the present invention that the cementitious powder of the present invention has suitable flow properties. Therefore, it can be stored in silos and handled without risk of clogging or without significant viscoelastic and rather unpredictable flow behavior.
[0077] The cement-based powders are shown to be suitable for reuse of fiber cement. Tests have shown that the normalized strength is increased compared to fiber cement without the corresponding component of recycled fiber cement. The invention produces a product with a higher Young's modulus and a higher level of elastic behavior compared to fiber cement comminuted according to the process of the invention but without removing the fibers by screening.
[0078] Preferred manufacturing methods for fiber cement products include the Magnani process, extrusion process, flow process and Hatschek process. The Hatschek process is most preferred. More preferably, cement-based powders are used to produce fiber cement products with medium or high density, such as fiber cement sheets. Medium density fiber cement products are designated as having a density of 1.2-1.5 g / cm 3 The density of the high-density product is at least 1.5 g / cm 3 , usually 1.5-2.0g / cm 3 .
[0079] Cement-based powders have further proven to be suitable for concrete production. Here, the CSH content can contribute to additional strength. In addition, since most of the fibers are removed, the water requirement is reduced when such powders are reused in concrete manufacturing.
[0080] Cement-based powder is suitably used in an amount of at least 7% by weight, for example 10-20% by weight, such as 15% by weight in the example shown. However, it is not excluded that cement-based powder is used in larger amounts, for example greater than 20-50% by weight. BRIEF DESCRIPTION OF THE DRAWINGS
[0081] These and other aspects of the method, the apparatus of the invention and the resulting powder will be further elucidated with reference to the accompanying drawings and examples. For the sake of completeness, it is observed that any preferred embodiment or implementation discussed above and / or specified in one or more dependent claims applies to all aspects of the invention, even if not explicitly specified for the sake of brevity. In the drawings:
[0082] Figure 1 1 is a conceptual diagram of various stages of a method according to an embodiment of the present invention. The figure also provides a schematic diagram of the main components of a facility according to an embodiment of the present invention. DETAILED DESCRIPTION
[0083] The steps of the method of the present invention and the components of the installation will be described in more detail below, including possible alternatives included in the scope of protection and preferred ranges for multiple parameters. However, unless also stated in the independent claims, the stated details do not limit the scope of protection.
[0084] The step of breaking the fiber cement blocks into broken material fragments can be carried out in two stages depending on the size of the raw material blocks. In most cases, these blocks will be so large that a comminution stage is required to reduce the material to blocks with a maximum size of about a few centimeters to 20 centimeters, hence the term "centimeter-scale" or agglomerated material. Comminutor facilities known in the art can be used for this purpose.
[0085] Reference Figure 1 , the supply of such agglomerated material is loaded into a hopper 1 or any other equivalent supply means. These lumps may be produced by a pulverizer facility (not shown) and are supplied to the hopper 1 continuously or in batches, from which they are conveyed on a first conveyor belt 2 to a hammer mill 3, which is configured to break the agglomerated material into broken material having a diameter of about 3 mm to 5 cm. Preferably, the diameter of the broken material is less than about 10 mm. The term "diameter" is used to indicate the size of the material, but the material lumps are not necessarily spherical in a geometric sense in terms of the microscopic scale. However, in terms of the macroscopic scale, the material lumps closely resemble spheres, so that the diameter can be determined with an accuracy of the order of millimeters (for example, a lumps with a diameter of 5 mm can be distinguished from a lumps with a diameter of 8 mm). Preferably, the minimum size is not too small to avoid that the fibers will be exposed and / or significantly ground before entering the micronization device.
[0086] The hammer mill 3 may be any type of equipment known in the art and is suitable for breaking up the agglomerated material blocks of waste fiber cement material into broken materials having the above-mentioned sizes. As shown in the figure, the hammer mill 3 may include a rotating hammer arm 4 and a screen 5 that allows the fragments to pass through the screen depending on their size. The hammer mill 3 is represented in a very simplified manner, but its function is known to those skilled in the art and therefore does not need to be described in detail here.
[0087] The pieces of agglomerated material are still large enough to contain the fibres embedded in a solid cement matrix, ie at this stage the fibres have not yet separated from the cement.
[0088] From the hammer mill 3, the crushed material is conveyed to the micronization device 10 by the second conveyor belt 6. As shown in the figure, the device is a special type of device, including a vertical roller mill in a grinding chamber 9, and an air classifier 14. The air classifier is arranged at the top of the grinding chamber 9. It may include a separate chamber in which separation is achieved by means of centrifugal force. The vertical roller mill shown includes a horizontally placed rotatable table 11 and a plurality of rollers 12, the rollers being positioned so that the lateral surfaces of the rollers face the grinding track 13 on the table 11. Preferably, the lateral surfaces of the rollers 12 are conical surfaces as shown in the figure. The rollers 12 actively rotate around their respective rotation axes and press against the rotating table 11, while the material is supplied to the space between the rollers 12 and the rotating grinding track 13, thereby further crushing the fragments into smaller particles. The air classifier 14 is installed above the rotor. In the embodiment shown, the air classifier 14 includes a ventilator 15 and a separation blade (not shown in detail). Not shown is an air inlet at the bottom side of the grinding chamber 9 through which air is pushed into the grinding chamber to create an upward air flow. An outlet duct 17 is connected to the outlet 16 .
[0089] In the grinding section of the vertical roller mill 10, the crushed material is ground between the rollers 12 and the grinding track 13, thereby forming cement-based particles. These particles can be "micron-sized". The term "micron-sized" means that these particles can be regarded as spheres on a microscopic scale and the accuracy is in the micron level, that is, a particle with a diameter of 20 μm can be distinguished from a particle with a diameter of 25 μm, 30 μm or 40 μm.
[0090] When these particles are as small as 100 μm or less in diameter, they become separated from the fibers, most of which are about 800 to 2000 μm in length when embedded in the cement matrix. The size reduction of the particles is more profound than the reduction in fiber length. It will be appreciated that grinding in a vertical roller mill causes the formation of agglomerates of the fibers and cement-based particles, i.e., materials held together by capillary forces and / or other physical attractions.
[0091] The stream of ground material is then lifted by the upward air flow out of the grinding area and passes through the blades of the air classifier 14. During the lifting process, the ground material dries. Due to the drying, the capillary forces and other physical bonds between the fibers and particles will be reduced. As a result, the ground material, i.e. the agglomerates, may disintegrate. It is not excluded that the interaction with the air classifier helps to achieve this separation.
[0092] The classifier is configured to allow only separated fibers and lighter, finer particles to pass through the blades, while coarser particles fall back to the grinding area. The finer particles correspond mainly to the fraction of particles with a diameter of about 100 μm or less, i.e. particles that are substantially free of embedded fibers. The larger particles are ground again until they also break apart into smaller particles separated from the fibers. Thus, the mixture of fibers and particles that passes through the outlet 16 and enters the outlet pipe 17 is a mixture of mostly unbroken fibers and cement-based particles of micrometer size.
[0093] The sieving step is carried out in a screen 20 comprising a mesh 21 with holes designed to retain fibers and allow cement-based particles with a diameter of 100 μm or less to pass through the mesh and fall through an outlet conduit 22, from which the particles can be collected as the final product of the method. For example, the mesh openings can be, for example, circular or equivalent, with a diameter of about 60 μm to 200 μm. According to a further embodiment, the diameter of the mesh is in the range between 50 μm and 150 μm. According to a specific embodiment, the mesh diameter is about 100 μm. The screen 20 can be any type of screen capable of carrying out the sieving step as described above. For example, it can be a roller screen. It can also be an ultrasonic screen.
[0094] The fact that a large portion of the fibers are not broken up in the grinding zone of the roller / classifier mill 10 enables the use of a screen having the above-mentioned mesh openings, which would not be able to retain a sufficient amount of fiber material if a large portion of the fibers were broken up. This is believed to be a key factor in the ability of the method and apparatus of the present invention to achieve excellent results in terms of fiber content in the final product collected in the outlet conduit 22 of the screen 20.
[0095] The final product is a cementitious powder formed by particles having a diameter of about 100 μm or less and a fiber concentration of less than 2 wt% (weight percentage), the fiber concentration wt% being defined by means of the organic carbon content. According to a first embodiment, the fiber concentration is between 1 and 1.9 wt%, or between 1.2 and 1.9 wt%, or between 1.2 and 1.8 wt%, or between 1.3 and 1.7 wt%, or less than 1.5 wt%, or less than 1.4 wt% (all defined by the organic carbon content). According to a second embodiment, the fiber concentration is reduced to less than 1.4 wt%, more specifically, in the range of 0.5-1.4 wt%, such as 0.5-1.2 wt% or even 0.5-1.0 wt%, as defined by the organic carbon content. The determination of the organic carbon content is achieved by means of treatment with a sufficiently strong acid, such as phosphoric acid, to remove any inorganic carbon. Thereafter, the sample is dried, oxidized and combusted, wherein the flow of CO2 is measured using a non-dispersive infrared detection unit.
[0096] The low fiber content enables the use of the powder as a resource for the production of new cement or fiber cement products, in other words, it enables full recycling of the original waste product.
[0097] According to a preferred embodiment, the cement-based particles obtained in the vertical mill are dried before or during transport to the classifier 14 by heating the mill 10. This can be done by heating the upward air flow that transports the particles towards the classifier 14. According to a preferred embodiment, the mill is heated to a temperature between 70° C. and 90° C. This can be achieved by heating the air flow to a temperature of about 200° C.
[0098] In addition to the temperature in the grinding chamber 9, optimization of many other parameters has proven to be beneficial in minimizing the fiber content and obtaining particles of the appropriate size in the final product. These parameters include the mechanical pressure applied to the rollers, the feed rate of millimeter-sized fragments into the roller / classifier mill 10, and the air flow rate in the mill 10.
[0099] The method of the present invention can be carried out as a continuous process, wherein a continuous supply of waste products is successively subjected to the various steps. Figure 1 Alternatively, the method may be carried out in a batch mode, wherein batches of waste products are processed according to each method step, wherein the final product of each step is transported to the next step as a batch of material.
[0100] The invention also relates to an installation suitable for carrying out the method of the invention. Such an installation comprises at least a roller / classifying mill 10 of the type described above, and a screen 20 of any type suitable for separating the fibers from the micron-sized cement-based particles.
[0101] exist Figure 1 In the embodiment shown, the plant also comprises a hammer mill 3 or any equivalent means capable of performing the same reduction of agglomerated material masses of the fiber cement waste material into broken material.
[0102] The transport of the product from one component to another need not necessarily be achieved by a conveyor belt as shown, but may be done by any other suitable transport means. The plant may additionally comprise a pulverizer placed upstream of the hammer mill 3 .
[0103] According to an embodiment of the method, a color separation step is added upstream of the micronization device, i.e. the pulverized material is subjected to color separation. The color separation step may include known separation means, such as a tool using a camera system. A corresponding embodiment of the plant of the invention includes said color separation means between the hammer mill 3 or its equivalent and the micronization device 10.
[0104] Example 1
[0105] The cement-based powder obtained by the process of the present invention has been characterized. Table 1 shows test data obtained using waste material for autoclave-cured fiber cement products. The waste material was obtained by Eternit NV under the trade name Tectiva TM Cutting waste generated during the production of commercial autoclave-cured fiber cement products. Figure 1 As described, the material was processed with the aid of a micronizing device. The particle size of the pulverized material was less than 5 mm. The material was processed to a size of less than 100 μm using a vertical roller mill. For the purpose of the experiment, samples were taken without sieving, using a sieve with a 100 μm mesh and a sieve with a 150 μm mesh. The sieve was an air jet sieve without the use of an ultrasonic system. The organic carbon content and bulk density were measured using standard methods. The particle size distribution was measured using a Malvern Mastersizer 3000 device using laser diffraction.
[0106] Table 1
[0107]
[0108] From the data in this table it is clear that sieving has a significant effect on the organic carbon content. In addition, the organic carbon content obtained with a sieve having a mesh of 100 μm is significantly lower than that with a sieve having a mesh of 150 μm.
[0109] Furthermore, it can be seen that the resulting particle size distribution is concentrated in the range of 2 to 63 μm (D10 and D90 limits). In the example shown, the median value (D50) is between 15 and 20 microns. In other examples where the crushed material has a larger size and another vertical roller mill is used, a distribution is obtained using a sieve with a 150 μm mesh, where D10 is 2.4 μm, D50 is 24 μm, D75 is between 55 and 60 μm, and D90 is in the range of 110-140 μm.
[0110] Example 2
[0111] The test results of the air-curing cement-based powders are shown in Table 2. The fiber cement waste material was offcuts from fiber cement panels commercialized by Eternit NV under the name Natura.
[0112] Sieving was performed using a sieve with a 150 μm mesh.
[0113]
[0114] Table 2
[0115] The same trend experienced by the autoclave cured material can also be seen in this table. The organic carbon content is greatly reduced by sieving and the particle size distribution ranges from 2 μm (D10) to 93 μm (D90), thus slightly below 100 μm. The median value is 22 μm.
[0116] Example 3
[0117] Tests were conducted to determine the average fiber length in the sample after sieving. Here, materials sieved through a 150 μm sieve were used. This material, which includes both fiber and inorganic powder, was processed in a Resch vibrating screen oscillator for 5 minutes. In this device, sieves of 150 μm, 100 μm and 75 μm were used. On each sieve, a fiber-rich layer was produced on the top of the inorganic powder. After this, the fiber-rich layer was removed from the inorganic powder and merged into a fiber sample. The removed fiber sample still includes inorganic powder. However, this contamination is small enough, so it will not hinder or interfere with the operation of the measuring device. It was observed that the fiber-rich layer was the thickest on the 150 μm sieve and the thinnest on the 75 μm sieve.
[0118] Thereafter, the average fiber length is determined on the separated fibers with the aid of a Valmet FS5 device, which is a fiber image analyzer for automatic fiber measurement. The device includes a camera that uses UHD (Ultra High Density) image resolution, which cameras are also commercially available, such as 4K resolution with 4096 x 2160 pixels. The fiber length is measured by the device according to the ISO16065-2 standard, therefore using non-polarized light.
[0119] The measured fiber length can be specified in different ways. A distinction is made between the arithmetic mean length L(n) of the fiber, as can be obtained by optical microscopy, and the length-weight average fiber length L(i), as is commonly used in the wood pulp industry. Here:
[0120] L(n) = ∑(ni *li) / ∑(ni) (1)
[0121] L(i)=∑([li*ni]*li) / ∑[li*ni](2).
[0122] The ratio of two different average fiber lengths (L(i) / L(n)) is the polydispersity, a measure of the breadth of the length distribution.
[0123] The average fiber length was determined for the cement-based powders obtained after sieving through a 150 μm sieve according to Examples 1 and 2 (Samples 1 and 2, respectively). In addition, the average fiber length was determined for another cement-based powder obtained from autoclave-cured production waste (Sample 3) and for a reference sample. The reference sample was a fresh cellulose mixture used in an autoclave-cured fiber cement composition.
[0124] The results are shown in Table 3
[0125] sample Curing technology L(n)(mm) L(i)(mm) L(i) / L(n) 1 Autoclave curing 0.33 0.38 1.15 2 Air curing 0.40 0.46 1.15 3 Autoclave curing 0.33 0.38 1.15 refer to none. 0.88 1.54 1.75
[0126] Table 3
[0127] The material of sample 3 was sieved through a 150 μm sieve, a 100 μm sieve and a 75 μm sieve. The results are as follows:
[0128] As shown in Table 4
[0129] sample Screen size L(n)(mm) L(i)(mm) L(i) / L(n) 3(1) 75μm 0.28 0.30 1.07 3(2) 100μm 0.37 0.40 1.08 3(3) 150μm 0.51 0.56 1.10
[0130] Table 4
[0131] From the results in Table 3, it can be concluded that the arithmetic mean length L(n) of the fibers in the cement-based powder is in the range of 0.30 mm to 0.45 mm, the length weight average length L is in the range of 0.35 mm to 0.50 mm, and the polydispersity L(i) / L(n) is in the range of 1.10-1.20. It is obvious that the average fiber length is well above the sieve fraction of 150 μm.
[0132] Compared to fresh fibers, the average length is significantly shorter. In fact, considering that about one third of the fiber weight is removed and the fiber length is reduced to 30-50%, such as 35-40% (0.33 / 0.88=0.375), the total fiber number per unit mass of cement-based powder will be greater than the fiber number in the waste material (or fresh material).
[0133] In addition, compared with the sample of fresh cellulose fiber, polydispersity is reduced. Low polydispersity indicates that fiber is not yet pulverized. In addition, what this low polydispersity indicates is that cement-based powder is useful for being reused in various cement-based products, such as fiber cement products, concrete, mortar and cement materials. Due to the relatively short length of fiber, cement-based powder has good dispersibility. This is important, so fiber cement composition can include a large amount of cement-based powder, such as at least 15%. From example 4, it is obvious that the fiber cement product made in Hatschek process has a composition (compared with reference, with the amount of cement and silica reduced) comprising 15% by weight of this cement-based powder, and has higher IMOR and dMOR compared with reference. In addition, compared with the sample comprising cement-based powder from unscreened discarded fiber cement material, also have the E-modulus of increase.
[0134] Example 4
[0135] Further tests were carried out using cement-based powder as characterized in Table 1. This material was added to the slurry used to make fiber cement. The slurry composition was according to Tectiva board, with the difference that the amount of Portland cement and silica was reduced, and 15% of cement-based powder was added. The other ingredients remained the same. The ingredients are shown in Table 5. The amounts indicated are based on dry weight. The tests were carried out using a composition that did not contain any recycled material, a composition that was only ground, and a composition that was ground and sieved using a sieve with a 150 μm mesh.
[0136]
[0137] Table 5 - Composition
[0138] The slurry was used to make fiber cement sheets using a pilot line for the Hatschek process (small Hatschek). The resulting panels had 20 layers of film and a total thickness of 8 mm. 2 Press them down with 10% pressure for 10 minutes.
[0139] The pretreatment was carried out overnight at room temperature. Subsequently, the panels were cured in an autoclave apparatus at 170°C for 12 hours.
[0140] The resulting panels were then tested to identify their mechanical properties as well as their chemical composition, namely the organic content and the amount of tobermorite.
[0141] Table 6 - Test results, determined under air drying conditions *, after drying at 40°C for 3 days, m% are mass percentages based on the dry weight of the composition.
[0142]
[0143]
[0144] The test results show that the organic carbon content increases relative to the fresh product. However, the content of the sieved sample is lower than that of the unsieved sample. Considering the addition of fresh cellulose fibers, the total organic carbon content is higher than 2%.
[0145] Due to the addition of recycled cement-based powder, the density of the product decreases. However, it must be taken into account that the amount of fresh cement in the samples with recycled powder is lower. This is not surprising since the density of cement is higher than recycled cement-based powder (containing about one third of cement).
[0146] The tobermorite content demonstrated a significant increase, from 17% to about 25%. This is clearly due to the addition of recycled fiber cement. The increase was beyond expectations based on the 15% addition of cementitious powder. It is believed that the presence of tobermorite in the cementitious powder may act as a nucleating agent for the formation of tobermorite during the autoclave curing process.
[0147] The mechanical properties shown are determined under air-dry conditions. SLOP is the strength value at the limit of proportionality between strain and material expansion. Beyond this value, deformation is irreversible and the material is damaged. SMOR is the bending strength determined by the modulus of rupture. dLOP and dMOR define the bending under SLOP and SMOR conditions. iMOR is the fracture energy. MOR / d 2 is the normalized flexural strength, where SMOR is divided by the square of the density.
[0148] As is evident from Table 6, the removal of the fibers brings the elastic properties of the product (i.e., elastic modulus and SLOP) to a level corresponding to a fresh product without any recycled material. This is a beneficial consequence of the removal of the fibers. The dMOR and iMOR increase relative to the fresh material, and the moisture content decreases. The SMOR value decreases slightly (a few percent). However, the normalized flexural strength increases due to the lower density.
Claims
1. A method for processing fiber cement waste material into cement-based powder, comprising the following steps: - supplying crushed material originating from fiber cement waste material to a micronization device (10), said micronization device (10) comprising: - Vertical roller mill in a grinding chamber; - means for generating an upward heated air flow through the grinding chamber; - an air classifier arranged above the vertical roller mill in the grinding chamber, and - an outlet downstream of said air classifier; - grinding the crushed material in the vertical roller mill to break up the crushed material, thereby reducing the size of at least a portion of the crushed material without correspondingly reducing the size of fibers embedded in the crushed material, thereby providing agglomerates of fibers and cement-based particles, - removing material from the vertical roller mill and drying the agglomerates with the fibers and the cementitious particles by means of an upward heated air flow, wherein the fibers and / or the cementitious particles are released from the agglomerates during the upward air flow and / or during any subsequent impact in the grinding chamber; - separating the cement-based particles into a portion of larger particles and a portion of smaller particles in the air classifier (14), the larger particles being re-supplied into the grinding chamber of the vertical roller mill, while the mixture of smaller particles and released fibers is ejected through the outlet (16), - Separating said sprayed mixture by means of sieving through a sieve so as to separate at least part of the released fibers from said cement-based particles, thereby obtaining said cement-based powder.
2. The method according to claim 1, characterized in that The grinding step is performed by compressing the crushed material.
3. The method according to claim 1 or 2, characterized in that: The air classifier is arranged to have a classification point in the range of 75 to 125 μm, preferably 90 to 110 μm, and wherein the vertical roller mill is arranged to have a grinding size in the range of 75 to 125 μm.
4. The method according to any one of claims 1 to 2, characterized in that The separation of the sprayed mixture is performed by sieving with a sieve having a mesh of at most 150 microns, preferably at most 125 microns, and preferably at least 50 microns, more preferably at least 75 microns.
5. The method according to any one of the preceding claims, characterized in that The grinding chamber is preferably heated to a temperature between 70° C. and 90° C. by means of the heated gas flow.
6. The method according to any one of the preceding claims, characterized in that The resulting cement-based powder has an organic carbon content of at most 2% by weight.
7. A method according to any one of the preceding claims, further comprising a color-based separation step before the crushed material enters the micronization device.
8. The method according to any one of the preceding claims, characterized in that The crushed material is provided by fiber cement waste material obtained by means of a first size reduction step and a second size reduction step, wherein the first size reduction step results in agglomerated material and the second size reduction step results in crushed material, wherein preferably the first size reduction step is performed by comminution and / or wherein preferably the second size reduction step is performed in a hammer mill.
9. The method according to any one of the preceding claims, characterized in that The crushed material has a particle size distribution with d50 in the range of 1-3 mm.
10. The method according to claim 8 or 9, characterized in that: Also included is a sorting step between the first size reduction step and the second size reduction step, wherein the sorting step is configured to remove materials different from fiber cement, such as polymer strips, and wherein the sorting step preferably includes a detection step using near infrared spectroscopy.
11. The method according to any one of the preceding claims, characterized in that The cementitious powder has a particle size distribution such that at least 90% by weight (d90) are less than 100 μm and the median (d50) is in the range of 10-40 μm, preferably 15-35 μm, more preferably 20-30 μm.
12. The method according to any one of the preceding claims, characterized in that Fiber cement waste material having a density measured according to EN 12467 of at least 1200 kg / m3 is processed.
13. The method according to any one of the preceding claims, characterized in that The fiber cement waste material is processed to include an air-cured cementitious material having at least 60 wt% cement or an autoclave-cured cement obtained from an autoclave-cured composition including silica and at least 25 wt% cement.
14. A facility for processing waste fiber cement material comprising: - an apparatus for crushing waste fiber cement material in which the fibers are embedded in a cured cement matrix into a crushed material; - A micronization device (10), comprising: (i) a vertical roller mill in a grinding chamber, the vertical roller mill being configured to use the crushed material as a feed and to generate agglomerates of cement-based particles and fibers from the crushed material; (ii) means for generating an upward heated air flow through the grinding chamber, wherein the heated air flow is configured to transport the agglomerates, fibers, and the cement-based particles upwardly and to dry the agglomerates; (iii) an air classifier arranged in the grinding chamber above the vertical roller mill for separating a coarser fraction of the cementitious particles and returning them into the grinding chamber towards the vertical roller mill, and an outlet downstream of the air classifier through which a finer fraction with the cementitious particles and released fibers passes; - A screen downstream of said outlet for separating said released fibers from said cement-based particles.
15. The facility according to claim 14, characterized in that The vertical roller mill comprises a rotating horizontal grinding track (13), one or more rollers (12), the rollers (12) being configured to rotate about a fixed rotation axis while pressing against the grinding track, whereby the crushed material is ground between the grinding track (13) and the lateral surfaces of the rollers (12).
16. The facility according to claim 14 or 15, characterized in that The screen (20) is configured to separate the fibers of the mixture from the particles by using a mesh (21) having openings configured to allow a majority of the particles to pass through while retaining a majority of the fibers, wherein preferably the diameter of the openings of the mesh (21) is between 60 μm and 200 μm or between 50 μm and 150 μm.
17. The facility according to any one of claims 14 to 16, characterized in that The means for generating an air flow comprises an air inlet at a bottom side of said grinding chamber to produce said upward air flow.
18. The facility according to any one of claims 14 to 17, characterized in that The micronization apparatus comprises a first output and a second output, and further comprises a displacement device for displacing solid material from the vertical roller mill to the second output.
19. The facility according to claim 18, characterized in that The first output is arranged at a lower level than the second output and at a lower level than the vertical roller mill, and is configured for removing aggregate.
20. The facility according to claim 18 or 19, characterized in that The micronizing apparatus is configured to have a first state and a second state, in which the setting of the vertical roller mill is different from that in the second state, and in the first state, the vertical roller mill is configured to grind concrete or its crushed material, and in the second state, the vertical roller mill is configured to grind crushed material from fiber cement waste material into agglomerates of fibers and cement-based particles.
21. Use of the plant according to any one of claims 18 to 20 for separate processing of a first batch and a second batch of waste material, wherein the first batch is concrete waste material and the second batch is fiber cement waste material.
Citation Information
Patent Citations
Superfine pulverizing method for waste material
JP2002273258A
Fiber reinforced cement board and its manufacturing method
JP2004217482A
Microscope with focusing detection device
JP2006023624A
Cited By
Industrial waste material dynamic grading evaluation system and method
CN120744712A
Light particle wrapping equipment and method based on solid waste treatment
CN120841869A